2005
DOI: 10.1016/j.ijdevneu.2005.07.003
|View full text |Cite
|
Sign up to set email alerts
|

IGF‐1 and BDNF promote chick bulbospinal neurite outgrowth in vitro

Abstract: Injured neurons in the CNS do not experience significant functional regeneration and so spinal cord insult often results in permanently compromised locomotor ability. The capability of a severed axon to re-grow is thought to depend on numerous factors, one of which is the decreased availability of neurotrophic factors. Application of trophic factors to axotomized neurons has been shown to enhance survival and neurite outgrowth. Although brainstem-spinal connections play a pivotal role in motor dysfunction afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…It indicated strongly that the increased endogenous IGF-I expressions in the spared L 6 DRG and the associated spinal dorsal horns were responsible for the sprouting phenomenon. This was supported by previous work which showed that the administration of IGF-I specifically enhanced the extent and rate of axonal outgrowth of the murine corticospinal motor neurons [25], and the axonal outgrowth of injured neurons in the CNS [26]. Also, Ang LC found that IGF-I have neurotrophic activity for motoneurons, an effect possibly mediated by living astrocytes [27].…”
Section: Effects Of Partial Ganglionectomies On Igf-i Expressionssupporting
confidence: 71%
“…It indicated strongly that the increased endogenous IGF-I expressions in the spared L 6 DRG and the associated spinal dorsal horns were responsible for the sprouting phenomenon. This was supported by previous work which showed that the administration of IGF-I specifically enhanced the extent and rate of axonal outgrowth of the murine corticospinal motor neurons [25], and the axonal outgrowth of injured neurons in the CNS [26]. Also, Ang LC found that IGF-I have neurotrophic activity for motoneurons, an effect possibly mediated by living astrocytes [27].…”
Section: Effects Of Partial Ganglionectomies On Igf-i Expressionssupporting
confidence: 71%
“…For example, brain-derived neurotrophic factor (BDNF) and insulin-like growth factor (IGF-1) were shown to be involved in nerve regeneration. 26 Future experiments will examine this issue in the case of hair follicle stem cells.…”
Section: Resultsmentioning
confidence: 99%
“…BDNF is now also known as a modulator of neurotransmission and synaptic plasticity in the central and peripheral nervous systems (CNS and PNS, respectively) and for its role in neurite growth (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). In addition to these classical functions, evidence is emerging that BDNF has a broader role in nervous system functionality.…”
mentioning
confidence: 99%